Pemanfaatan Non Edible Oils Sebagai Bahan Baku Produksi Biodiesel Melalui Proses Transesterifikasi Menggunakan Metode Elektrolisis - andrianto, muhamad; Putra, Catur Wahyu Cornelis; Wibowo, Sugeng Arief; Rosid, Fathor; Prasetya, Yahya Ade Wahyu (Politeknik Negeri Jember, 2025)
Electrolysis is a process where chemical reactions occur on electrodes immersed in an electrolyte, when a voltage is applied to the electrodes. This research aims to get recommendations for the best process stages using the electrolysis method in the transesterification reaction. The method used in this research is experimental with test results described using bar graphs. The results of the research using the electrolysis method for the transesterification process of non-edible oil can produce a fairly good biodiesel conversion. However, it is necessary to modify the pretreatment process on non-edible oil raw materials so that all test results can be in accordance with SNI 7182: 2015